The role of temperature on Cr(VI) formation and reduction during heating of chromium-containing sludge in the presence of CaO. (November 2015) - Mao, Linqiang; Gao, Bingying; Deng, Ning; Zhai, Jianping; Zhao, Yongbin; Li, Qin; Cui, Hao
Graphical abstract: Highlights: CaO results in Cr(III) being oxidized to Cr2 O3+ x annealed at 200–400 °C. Most of Cr2 O3+ x would be reduced into Cr2 O3 over 400 °C. Part of CaCrO4 is reduced to Ca(CrO2 )2 at 1000–1200 °C. Ca(CrO2 )2 is oxidized reversibly to CaCrO4 annealed at 1200 °C over 1 h. Abstract: In this study, the temperature dependence of Cr(VI) formation and reduction in the presence of CaO was examined during the thermal treatment of sludge that contains chromium. thermogravimetry–differential scanning calorimetry and X-ray diffractometry were used to characterize the thermal behavior and phase transformation, respectively. Na2 CO3 leaching procedure was employed to determine the amount of Cr(VI). The result showed that CaO promoted Cr(III) oxidation, however, its influence is very dependent on heating temperature, with the extent of the effect varying with temperature. From 200–400 °C, the presence of CaO facilitated formation of intermediate product Cr2 O3+ x containing Cr(VI) during dehydration of chromium hydrate, while Cr2 O3+ x would decompose as temperature over 400 °C, accompanied by part of Cr(VI) being reduced to Cr(III). From 500 to 900 °C, Cr(III) reacted with CaO to form a leachable CaCrO4 product. This product was stable and a prolonged heating time did not reduce the amount of Cr(VI) significantly. At 1000–1200 °C, part of CaCrO4 was reduced to Ca(CrO2 )2 in 1 h. While extended heating time above 1 h resulted in the Ca(CrO2 )2 being oxidized reversibly to CaCrO4 at 1200 °C. Since CaCrO4 is thermodynamically less stable over 1000 °C, MgO could induce CaCrO4 to be reduced into MgCr2 O4 at around 900 °C, lower than that for the reduction from CaCrO4 into Ca(CrO2 )2 . It suggested that adding MgO might be a potential approach for inhibiting Cr(VI) formation during heating sludge containing chromium.